Incomplete Land Redistribution and Compensation Rights: Legal Obstacles in Implementing Agrarian Reform for Absentee Land Exceeding Maximum Limits - R. Pursita Ayu Gandari Kartanegara; Deden Sumantry (Magister Kenotariatan Universitas Pasundan, 2025)
The Agrarian Reform program mandates the redistribution of absentee land exceeding the maximum limit to ensure equitable land tenure among farmers. This study examines the implementation of land redistribution in a rural area of West Java Province, where approximately 263 hectares of individually owned customary land were designated for redistribution. However, only 164 hectares have been redistributed, with compensation provided to the original owners, leaving approximately 99 hectares undistributed and former owners without compensation. This research employs a juridical-normative approach, using descriptive-analytical methods, collecting data through library research and field studies, and analysing them qualitatively. The findings reveal three principal issues. First, incomplete redistribution creates legal uncertainty regarding land status and undermines the rights of both prospective beneficiaries and former landowners. Second, two forms of repressive legal protection are available to former landowners who have not received compensation: non-litigation mechanisms through administrative channels and litigation mechanisms through judicial proceedings. Third, obstacles to redistribution encompass both legal factors, such as regulatory gaps and the absence of enforceable sanctions against government inaction, and non-legal factors, such as administrative inefficiency and budgetary constraints. To address legal barriers, affected parties may file a judicial review petition with the Constitutional Court challenging the constitutionality of the prevailing land reform regulations. This study recommends regulatory reform to establish precise enforcement mechanisms, accelerated compensation procedures, and institutional accountability measures to complete the redistribution process and achieve the objectives of Agrarian Reform.